Geometric Design and Pavement Analysis of Kopi Luhur Road, Argasunya Village: A Case Study in Cirebon Regency - Isradi, Muhammad; Setyani, Mery; Prasetyo, Adi; Tamabitte, Vhena E; Dermawan, Widodo Budi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Street Kopi Luhur, located in Argasunya Village, Harjamukti District, Cirebon City, is a local road that plays a strategic role as the main access for residents to housing areas and centers of local economic activity. The research employed a descriptive quantitative approach. Primary data were obtained through direct field surveys, including visual inspections and measurements of pavement conditions, while secondary data were collected from relevant local government agencies. The analysis of pavement conditions was conducted using the Road Condition Index (RCI) method to determine the level of damage, whereas traffic performance was evaluated based on the Indonesian Road Capacity Guidelines (PKJI, 2023) to determine the Level of Service (LOS) and the Degree of Saturation (Dj). The results indicate that the pavement condition of Street Kopi Luhur is generally categorized as moderate to severely damaged, with an average RCI value of 53, corresponding to a class D service level. The dominant forms of pavement distress include longitudinal cracking, potholes, and surface unevenness. These damages are mainly caused by inadequate drainage systems, high traffic loads, and limited maintenance activities. Furthermore, the Degree of Saturation (Dj) value of 0.79 shows that the road segment is approaching congested conditions, leading to reduced service performance. Based on these findings, recommended improvement measures include rehabilitation of the pavement structure using HRS-WC and Cement Treated Base (CTB) layers, enhancement of the roadside drainage system, and the implementation of a community-based periodic maintenance program.